Respuesta :

Hello, My Dear Friend!

Solution for [tex]4(5x-3)=48[/tex] equation:

Simplifying:
[tex]4(5x + -3) = 48[/tex]

Reorder the terms:
[tex]4(-3 + 5x) = 48[/tex]
[tex](-3 * 4 + 5x * 4) = 48[/tex]
[tex](-12 + 20x) = 48[/tex]

Solving:
[tex]-12 + 20x = 48[/tex]

Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '12' to each side of the equation.
[tex]-12 + 12 + 20x = 48 + 12[/tex]

Combine like terms: [tex]-12 + 12 = 0[/tex][tex]0 + 20x = 48 + 12[/tex]
[tex]20x = 48 + 12[/tex]

Combine like terms: [tex]48 + 12 = 60[/tex]
[tex]20x = 60[/tex]

Divide each side by '20'.
[tex]x = 3[/tex]

Simplifying:
[tex]x = 3[/tex]

Therefore, THAT is The Answer!^^^ 

=====> x = 3 <=====

I Hope my answer has come to your Help. Thank you for posting your question here in [tex]Brainly.[/tex] We hope to answer more of your questions and inquiries soon. Have a nice day ahead! :)

[tex](Ps. Mark As Brainliest IF Helped!)[/tex]

[tex]-UniteTheSeven, UniteTheLeague, Justice League!!! :D[/tex]

[tex]-TheOneAboveAll :)[/tex]
ACCESS MORE